THE EFFECT OF DISTANCE LEARNING ON VIRTUAL CLASSROOM MANAGEMENT BY ENGLISH LANGUAGE TEACHERS AT NABLUS PRIMARY GOVERNMENTAL SCHOOLS - Rizeq, Yasmeen (جامعة النجاح الوطنية, 2022)
The study aims at measuring the effect of distance learning on virtual classroom management by English language teachers at Nablus primary governmental schools. It also determines the obstacles of virtual classroom management during distance learning by English language teachers and suggests some appropriate solutions to these obstacles. To achieve the objectives of this study, the descriptive-analytical methodology is used. An online questionnaire is distributed to (231) male .The SPSS program is used to analyze the questionnaire data. Besides the questionnaire, the researcher chooses the online interview as a second tool for the study. The results show a high degree of possessing classroom management skills, technological skills, and evaluation skills and a very high degree of possessing the executive skills by English language teachers during distance learning at Nablus primary governmental schools. According to the study results, the researcher recommends conducting further studies about virtual classroom management during distance learning and providing teachers with strategies for managing virtual classrooms. The researcher suggests making use of digitalization revolution worldwide and distributing laptops or smart devices for both teachers and students.
THE EFFECT OF DISTANCE LEARNING ON VIRTUAL CLASSROOM MANAGEMENT BY ENGLISH LANGUAGE TEACHERS AT NABLUS PRIMARY GOVERNMENTAL SCHOOLS
The study aims at measuring the effect of distance learning on virtual classroom management by English language teachers at Nablus primary governmental schools. It also determines the obstacles of virtual classroom management during distance learning by English language teachers and suggests some appropriate solutions to these obstacles. To achieve the objectives of this study, the descriptive-analytical methodology is used. An online questionnaire is distributed to (231) male .The SPSS program is used to analyze the questionnaire data. Besides the questionnaire, the researcher chooses the online interview as a second tool for the study. The results show a high degree of possessing classroom management skills, technological skills, and evaluation skills and a very high degree of possessing the executive skills by English language teachers during distance learning at Nablus primary governmental schools. According to the study results, the researcher recommends conducting further studies about virtual classroom management during distance learning and providing teachers with strategies for managing virtual classrooms. The researcher suggests making use of digitalization revolution worldwide and distributing laptops or smart devices for both teachers and students.
Keywords: Distance Learning; Virtual Class Management; English Language Teachers; Governmental Schools.